2018
DOI: 10.1186/s13256-018-1641-z
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal paracoccidioidomycosis resembling Crohn’s disease in a teenager: a case report

Abstract: BackgroundDifferential diagnosis of inflammatory bowel disease is often very challenging. Paracoccidioidomycosis is a fungal disease that can mimic manifestations of Crohn’s disease.Case presentationWe report a case of a 13-year-old Caucasian boy with abdominal pain for 1.5 years associated with nausea, diarrhea, and weight loss of 10 kg. He presented increased C-reactive protein and an increased erythrocyte sedimentation rate. A colonoscopy showed deep serpiginous ulcers throughout his entire colon and rectum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
5
0
1
Order By: Relevance
“…A paracoccidioidomicose é uma doença fúngica que pode assemelhar-se às manifestações da doença de Crohn em pacientes de países endêmicos, uma vez que esta condição auto inflamatória crônica pode afetar qualquer parte do trato digestivo. Sendo assim, os pesquisadores sugerem que a PCM intestinal deve ser considerada como um diagnóstico diferencial para doença inflamatória intestinal em áreas endêmicas (Lomazi, et al, 2018). Research, Society and Development, v. 11, n. 3, e13911326152, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i3.26152 Buccheri, et al, (2018) demonstraram um relato de caso em que o paciente foi diagnosticado com a forma aguda (FA) da P. brasiliensis, porém 21 dias do início do tratamento o paciente fez uma triagem de rotina que acabou tendo resultados inconclusivos para P. brasiliensis anticorpos, entretanto teve resultados positivos com P. lutzii antígenos.…”
Section: Discussionunclassified
“…A paracoccidioidomicose é uma doença fúngica que pode assemelhar-se às manifestações da doença de Crohn em pacientes de países endêmicos, uma vez que esta condição auto inflamatória crônica pode afetar qualquer parte do trato digestivo. Sendo assim, os pesquisadores sugerem que a PCM intestinal deve ser considerada como um diagnóstico diferencial para doença inflamatória intestinal em áreas endêmicas (Lomazi, et al, 2018). Research, Society and Development, v. 11, n. 3, e13911326152, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i3.26152 Buccheri, et al, (2018) demonstraram um relato de caso em que o paciente foi diagnosticado com a forma aguda (FA) da P. brasiliensis, porém 21 dias do início do tratamento o paciente fez uma triagem de rotina que acabou tendo resultados inconclusivos para P. brasiliensis anticorpos, entretanto teve resultados positivos com P. lutzii antígenos.…”
Section: Discussionunclassified
“…PCM mimicking CD has been scarcely reported in the literature and in most reported cases the diagnosis came after several months of symptoms [5][6][7][8]. The wrong diagnosis led to immunosuppressive therapy leading to worsening of symptoms in some cases [6][7][8].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…PCM mimicking CD has been scarcely reported in the literature and in most reported cases the diagnosis came after several months of symptoms [5][6][7][8]. The wrong diagnosis led to immunosuppressive therapy leading to worsening of symptoms in some cases [6][7][8]. A recently published systematic review found 46 cases of gastrointestinal PCM predominantly in young men presenting the acute PCM form.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 For this reason, PCM should be considered in the differential diagnosis of inflammatory bowel diseases, specially in endemic countries, such as Brazil. 8 …”
Section: Introductionmentioning
confidence: 99%